The design of mosaic armour: the influence of tile size on ballistic performance - Hazell, Paul J.; Roberson, Colin J.; Moutinho, Mauricio (Cranfield University, 2008)
Silicon carbide square tiles of different areal geometries and manufactured via two different processing routes have been bonded to polycarbonate layers to evaluate their ballistic performance. Four ceramic tile sizes were tested: 85mm, 60 mm, 50 mm and 33 mm. In each case the residual depth-of-penetration into a polycarbonate semi-infinite backing was recorded. To elucidate the penetration and failure mechanisms, a computational model using the JH-1 ceramic model [Holmquist TJ, Johnson GR. Response of silicon carbide to high velocity impact. J Appl Phys 2002;91:5858–66] of the projectile used in the experimental study penetrating into a silicon carbide-faced polycarbonate was implemented in the hydrocode AUTODYN-2D. This paper shows that there is a critical dimension of tile that should be used in a silicon carbide-based ceramic-faced mosaic armour system design to ensure optimum system performance when each tile is struck centrally.
Keywords: engineering ceramics; impact and ballistics; failure analysis